Subjective usability review of “Sehat Jiwa” Apps - Putri Safirilla Ermadi (Berita Kedokteran Masyarakat (BKM), 2018)
Background: The prevalence of mental health problems in the Indonesian population increased significantly. The latest Riskesdas (Health Basic Survey 2018) reported that 9.8% of the population have an emotional mental disorder,  increased from 6.1% in the 2013 Riskesdas. In line with the growing number of mobile phone users (including those with a smartphone), Indonesian Ministry of Health has developed "Sehat Jiwa", a dedicated app for communication, information, and education related to mental health. Although this app that has been available in public since October 2015 and has been downloaded by around 1000 users, unfortunately, no usability review has been reported.Objective: To review “Sehat Jiwa” apps using assessment framework by Zelmer J et al (2018) that proposed 15 criteria in assessing e-mental health apps.Method: This subjective review was conducted from 29 October to 4 November 2018. Sehat Jiwa was downloaded from Google Play Store and installed in a mobile phone with an Android version. Installed apps occupied 18.93 MB storage. All features and functions of Sehat Jiwa were tested and evaluated.Result: The purpose of the app is to increase user’s awareness of mental health. Compared to the Zhelmer criteria, 8 out of 15 criteria are available which are effectiveness, functionality, usability, developer transparency, user desirability, audience, supported platforms, app price. Information about the remaining criteria including transparency of information security, information security, clinical criteria, funding transparency, user inclusion, meaningful inclusion, and interoperability are not available. “Sehat Jiwa” have a unique function on one of its feature, namely Deteksi Dini, when using this feature we will be able to see the score of our mental health condition through answering a few questions. There are three categories of questions, namely CAGE (Alcohol Addiction Detection), Self Reporting Questionnaire (SRQ) 20, and Geriatric Depression Scale (GDS) 15 for depression testing in the elderly. The app is free of charge and only compatible with an Android version of the mobile phone. The information given by this app is trusted because of Indonesian Ministry of Health is the Developer.Conclusion: “Sehat Jiwa” app contains 8 out of 15 criteria. It is recommended that Sehat Jiwa provide more information related with transparency information security, information security, clinical criteria, funding transparency, user inclusion, meaningful inclusion, interoperability. In general, this apps is user-friendly, informative and suitable for adolescences and adults user.  Given to this subjective nature of the assessment, more rigorous evaluation is needed for generalization.   Keywords: m-health, mental health, evaluation, usability